Leukocyte migration in experimental inflammatory bowel disease - E. P. Van Rees; M. J. H. J. Palmen; F. R. W. Van De Goot; B. A. Macher; L. A. Dieleman (Hindawi Limited, 1997)
Emigration of leukocytes from the circulation into tissue by transendothelial migration, is mediated subsequently by adhesion molecules such as selectins, chemokines and integrins. This multistep paradigm, with multiple molecular choices at each step, provides a diversity in signals. The influx of neutrophils, monocytes and lymphocytes into inflamed tissue is important in the pathogenesis of chronic inflammatory bowel disease. The importance of each of these groups of adhesion molecules in chronic inflammatory bowel disease, either in human disease or in animal models, will be discussed below. Furthermore, the possibilities of blocking these different steps in the process of leukocyte extravasation in an attempt to prevent further tissue damage, will be taken into account.